Fabrication and Mechanical characterization of aluminium [6061] with conventionally prepared bamboocharcoal. (2018) - Chethan, K.N.; Keni, Laxmikant G.; Padmaraj, N.H.; Dias, Abhijit; Jain, Rakesh
Abstract: In present day, the application of low cost material reinforced metal alloy is growing rapidly in different engineering fields [1]. The present study shows the possibilities of reinforcing Al 6061 alloy with conventionally prepared charcoal by using bamboo. The bamboo for the preparation of charcoal is initially divided into wet and dry samples. The wet samples are directly used after cutting from tree for the preparation of charcoal out of it and dry sample it is dried for 7days after cutting then used for preparation. The carbon content in both the samples is analysed by proximity analysis and elemental analysis by EDS (energy dispersive spectroscopy technique)[2]. Fine particles of bamboo charcoal of 2%, 4%, and 6% by weight were used to prepare the alloy by stir casting method. The fabricated alloys with different weight composition is normalized in 550°C for 6 hours and followed by different cooling techniques. The hardness and tensile properties were studied. It is found that the hardness of the Aluminium 6061 is going to be increased with increased in the concentration of bamboo charcoal and the tensile strength is going to be decreased with increased in the concentration of bamboo charcoal.